Diversity Insect Plant Jackfruit (Artocarpus Heterophyllus) on Land Orgosol, MARDI, Selangor, Malaysia - Muhammad Fachri Ansyida Ritonga; Wizni Fadhillah; Suhana Bt Yusuf (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
This study aims to identify and analyze the diversity of insect species on jackfruit (Artocarpus heterophyllus) plants in the MARDI organic farmland, Selangor, Malaysia. Data collection was conducted over 12 days, from September 23 to October 4, 2025, using two primary methods: Yellow Sticky Traps (YST) and manual capture. The data obtained included the number of individuals from various insect orders, including Hemiptera, Coleoptera, Diptera, Hymenoptera, Dictyoptera, Lepidoptera, and Orthoptera, as well as Arachnida, totaling 4,245 individuals. The results showed that the order Hymenoptera (predators) dominated with 1,589 individuals, followed by Hemiptera (600) and Diptera (beneficials) (463), while the lowest number was recorded in Orthoptera (6 individuals). The highest Shannon-Wiener diversity index (H') value was observed on day 6 (1.950), indicating a relatively balanced ecosystem, whereas the lowest value occurred on day 9 (1.597) due to the dominance of predatory Hymenoptera. The highest species richness (Margalef index) was also recorded on day 6 (2.88), indicating robust species diversity, and species similarity (Sorensen index) reached a maximum value of 1.0 on day 12, indicating the stability of the insect community. Overall, these results indicate fluctuating insect population dynamics, with a tendency toward ecosystem stability by the end of the observation period.